Measuring risk preferences in rural Ethiopia: Risk tolerance and exogenous income proxies - Ferdinand M. Vieider; Abebe Beyene; Randall Bluffstone; Sahan Dissanayake; Zenebe Gebreegziabher; Peter Martinsson; Alemu Mekonnen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
Risk aversion has generally been found to decrease in income or wealth. This may lead one to expect that poor countries will be more risk averse than rich countries. Recent comparative findings with students, however, suggest the opposite, giving rise to a riskincome paradox. We test this paradox by measuring the risk preferences of over 500 household heads spread over the highlands of Ethiopia. We do so using certainty equivalents, which have rarely been used in developing countries, but permit us to relate the findings to a host of evidence from the West. We find high degrees of risk tolerance, in agreement with the student comparisons finding higher risk tolerance in poorer countries. We also find risk tolerance to increase in income proxies, thus completing the paradox. We thereby use income proxies that can be considered as exogenous, allowing us to conclude that at least part of the causality must run from income to risk tolerance. We furthermore provide extensive methodological discussions on measuring and estimating risk preferences in development settings.
Keywords: C93; D03; D80; O12; 330; risk preferences; development; experimental methodology